Focal Muscle Vibration Improves Gait in Parkinson's Disease: A Pilot Randomized, Controlled Trial. Issue 6 (11th February 2016) - Camerota, Filippo; Celletti, Claudia; Suppa, Antonio; Galli, Manuela; Cimolin, Veronica; Filippi, Guido Maria; La Torre, Giuseppe; Albertini, Giorgio; Stocchi, Fabrizio; De Pandis, Maria Francesca
Abstract: Background: In Parkinson's disease (PD), gait disorders lead to increased risk of falls and patients' reduced participation and independence. Several observations suggest that a single session of focal muscle vibration (fMV) applied to trunk or lower limb muscles during gait may improve several gait variables in patients with PD. The possible long‐term beneficial effects of repetitive sessions of fMV (r‐fMV) on gait of patients with PD have been investigated. Methods: A randomized, controlled trial study has been conducted in an outpatient rehabilitation department. Twenty patients with PD diagnosis have been randomized in two groups: "real" or "sham" r‐fMV application to quadriceps and paraspinal muscles in patients with PD. Gait was evaluated with objective gait analysis, and a number of variables, including velocity, step length, stride length, percentage of stance, double support duration, cadence, swing velocity, and step width, have been measured. Gait analysis was performed before and 24 hours and 1 and 3 weeks after r‐fMV. Results: After real, but not sham, r‐fMV, patients with PD had significant gait improvement as a result of increased walking velocity and stride length. The r‐fMV‐induced beneficial after effects lasted at least 1 week after the end of stimulation. Conclusions: Data emerging from our pilot randomized, controlled trial study suggest that r‐fMV may improve gait disorders in patients with PD. r‐fMV might be a feasible, safe approach for possibly improving gait disorders in patients with PD and might enhance the impact of specific rehabilitation programs in PD.